STANDARDISASI MUTU FISIK EKSTRAK ETANOL DAUN SAWO MANILA (Manilkara zapota L.) DAN UJI POTENSI ANTIBAKTERI TERHADAP E.coli - A. Tenriugi Daeng Pine; Yuyun Sri Wahyuni; Nirmala Nirmala; A. Tenri Muji (Jurnal Kesehatan, 2019)
Quality inspection and standardization of traditional medicine raw materials is an important as the begining of  standardization of traditional medicines.  This study aims to determine  specific and nonspecific parameters physical standardization and to determinae any potential of sapodilla leaves (Manilkara zapota L.) ethanol extract  as an antibacterial against E.coli.  Simplisia of sapodilla leaf (Manilkara zapota L.) collected from Manjalling Village, West Bajeng District, Gowa Regency. Simplisia was extracted to produce thick extraxt by maceration using ethanol 96% as solvent.  The thick extract, then tested for specific parameters (identity, organoleptic), nonspecific (shrinkage drying) and its activity as an antibacterial against E.coli through paperdisc method. The results of this study showed that organoleptically the extract produced was  thick extract with a distinctive blackish-green (dark green) color, and bitter taste. Confirmed Identification of the plant name is Sapodilla (Manilkara zapota L.) known as sawo manilla in the local terms. The results for non-specific parameters by testing the drying shrinkage levels are an average of 79.5488%. this process aimed to provide maximum limits on the amount of compound lost in the drying process. The results for antibacterial activity against E. coli gained in extract concentration of 10% w/v   with 11 mm inhibition zone